Composing control flow and formula rules for computing on grids - Bottoni, Paolo; Mirenkov, Nikolay; Watanobe, Yutaka; Yoshioka, Rentaro (Electronic Communications of the EASST, 2008)
We define computation on grids as the composition, through pushout constructions, of control flows, carried across adjacency relations between grid cells, with formulas updating the value of some attribute. The approach is based on the identification of a subcategory of attributed typed graphs suitable to the definition of pushouts on grids, and is illustrated in the context of the Cyberfilm visual language.